2010
DOI: 10.1111/j.1399-3089.2010.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

The fate of human platelets perfused through the pig liver: implications for xenotransplantation

Abstract: Our observation of pig LSEC phagocytosis of human platelets describes a novel mechanism of large-particle uptake in the liver. The creation of a model system to study xenotransplantation-induced thrombocytopenia makes possible the investigation into mechanisms that mediate platelet loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
74
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 34 publications
6
74
1
Order By: Relevance
“…They also found that massive hemorrhage but not thrombocytopenia post pig liver xenotransplantation could be partially ameliorated with auxillary GE pig liver xenotransplantation [18]. (iii) In an in vitro study [27], they confirmed baboon platelet phagocytosis by pig aortic endothelial cells, which was previously shown by the Indianapolis group [20]. However, the pathway identified in this work [27] was integrin adhesion pathway involving vWF and MAC-1.…”
Section: Progress With Genetically-engineered Pigssupporting
confidence: 77%
“…They also found that massive hemorrhage but not thrombocytopenia post pig liver xenotransplantation could be partially ameliorated with auxillary GE pig liver xenotransplantation [18]. (iii) In an in vitro study [27], they confirmed baboon platelet phagocytosis by pig aortic endothelial cells, which was previously shown by the Indianapolis group [20]. However, the pathway identified in this work [27] was integrin adhesion pathway involving vWF and MAC-1.…”
Section: Progress With Genetically-engineered Pigssupporting
confidence: 77%
“…The latter appear to be important contributors to platelet uptake, as they efficiently phagocytised baboon platelets, whereas porcine aortic endothelial cells and hepatocytes had minimal effects on platelet number [78]. There was evidence of platelet degradation in LSEC 60-120 min after their perfusion [72].…”
Section: List Of Abbreviationsmentioning
confidence: 88%
“…Ex vivo pig liver perfusion with human platelets resulted in the removal of 93% of human platelets from the circulation after 15 min [72]. Platelets were shown to adhere to liver sinusoids [73] and to be sequestered by Kupffer cells and LSEC [72,[74][75][76][77]. The latter appear to be important contributors to platelet uptake, as they efficiently phagocytised baboon platelets, whereas porcine aortic endothelial cells and hepatocytes had minimal effects on platelet number [78].…”
Section: List Of Abbreviationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, it has been shown that porcine Kupffer cells and liver sinusoidal endothelial cells (LSEC) bind and phagocytose human platelets in ex vivo perfusion systems. 12 Many scavenger receptors have been reported on LSEC that facilitate the clearance of particulate, molecular, and cellular "waste" from the circulation, 13 one of them being the asialoglycoprotein receptor-1 (ASGR1). It functions as a recycling receptor, which mediates capture and phagocytosis of Galβ1-4-and GalNAcβ1-4-terminating glycoproteins.…”
mentioning
confidence: 99%